2012
DOI: 10.1353/ppp.2012.0006
|View full text |Cite
|
Sign up to set email alerts
|

Foucault’s Notion of Power and Current Psychiatric Practice

Abstract: Underlying Foucault’s accounts of asylums, hospitals, prisons, and schools was a continuing concern with power and knowledge. In the field of mental health, his preoccupation with power relations and the construction of narratives of exclusion and repression in the History of Madness have led many scholars to consider Foucault an anti-psychiatrist (Freeman 1967; Laing 1967; Leach 1967; Shorter 1997, 274). They question the book’s historical data, which prioritize power relations and political analysis over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In particular, participants suggested that aspects of the service user-provider relationship and medication use could serve to disempower service users under normal circumstances, some even going so far as to suggest they could metaphorically "imprison" service users; findings which reflect Foucauldian structuralist interpretations of the physical and metaphorical confinement historically associated with the discipline of psychiatry (Foucault, 2001;Iliopoulis, 2012). Gillett (2012) suggests that such "confinement" may be overcome if service providers choose to transcend rational systems of classification and objectification in their therapeutic relationships with service users.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, participants suggested that aspects of the service user-provider relationship and medication use could serve to disempower service users under normal circumstances, some even going so far as to suggest they could metaphorically "imprison" service users; findings which reflect Foucauldian structuralist interpretations of the physical and metaphorical confinement historically associated with the discipline of psychiatry (Foucault, 2001;Iliopoulis, 2012). Gillett (2012) suggests that such "confinement" may be overcome if service providers choose to transcend rational systems of classification and objectification in their therapeutic relationships with service users.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differences identified in the theories offered by these leading scholars, the assumption that there is a form of rationality behind the exercise of power is commonly accepted (Iliopoulos, 2012), and an up-down vertical path of power implementation through influence is suggested. The consideration of power in the effects of persuasion and negotiation is added into the theories, but the idea that influence produces power exercise through status-based expectancies is not yet clearly established (Willer, 1997).…”
Section: Quan (Power) and Shi: A Chinese Communication Theoretical Frmentioning
confidence: 99%
“…Even if nurses possessed all of this information, it still may not be helpful. John Iliopoulos 6 notes that psychiatrists, who have much more information than nurses about prisoner-patients’ criminal histories and backgrounds, have been unable to predict who is and is not dangerous, and argues that the attempt to do so has been harmful to psychiatry as a discipline. It thus seems unlikely that nurses are able to accurately predict whether a prisoner-patient is likely to be violent or aggressive based solely on the patient’s criminal history.…”
Section: Nurses’ Safety and Prisoner-patients’ Criminal Historiesmentioning
confidence: 99%